The Obligation to Use Bahasa Indonesia in National Trade: A Juridical Review - zaid, Zaid; Indrianto, Anggraeni Pratama; Dimas, Fathir Arya (International Journal of Social Science and Business, 2021)
Language is a very important essence and a very basic aspect. Therefore, every human being in various activities and life is always closely related to it. This includes trading. Considering that no research discusses the use of bahasa Indonesia in national trade, especially after passing the omnibus law on job creation, so by using the normative juridical method, this study aims to identify and analyze the need for the use of Indonesian which has emerged as the national language and the ideal official language as part of the from national identity in national trade to achieve fair trade. The results of this study ultimately conclude that the use of bahasa Indonesia in national trade is mandatory for every party, especially business actors in determining the inclusion of Indonesian on labels of goods and services that are distributed and traded domestically.